Removal of organic matter and oxides of iron and manganese from soil influences boron adsorption in soil - Sarkar, Dibyendu; De, Dipak Kumar; Das, Ruma; Mandal, Biswapati (Geoderma, 2014)
The influences of specific soil components such as organic matter and oxides of Fe and Mn on B adsorption characteristics are not understood well. In the present study, we compared B adsorption behavior of two acidic soils after removal of organic matter, and Fe- and Mn-oxides with that of untreated soil samples. The B adsorption capacity of the soils before and after removal of different components was low; the average values of maximum B adsorption obtained from nonlinear least square optimization of Langmuir adsorption isotherm being 20.61mgkg−1 for Mallerbari soil and 27.15mgkg−1 for Sikarpur soil. Removal of organic matter by NaOCl treatment from the soils increased B adsorption. This indicates that Fe- and Al-oxides and other available adsorption sites on the mineral surfaces are coated by organic matter and are activated only after removal of organic matter. Removal of Fe- and Mn-oxides, however, resulted considerable decrease in B adsorption in the soils. It is, therefore, suggested that B adsorbing surfaces in soil decrease on removal of Fe- and Mn-oxides, since these oxides are known to have good adsorptive capacity for B. •Low B adsorption is one of the reasons for B deficiency in light textured soils.•Removal of organic matter from soils increases B adsorption.•Removal of Fe- and Mn-oxides decreases B adsorption in soils.